Systematic RH genotyping and variant identification in French donors of African origin - Kappler-Gratias, Sandrine; Auxerre, Carine; Dubeaux, Isabelle; Beolet, Marylise; Ripaux, Maryline; Le Pennec, Pierre-Yves; Pham, Bach-Nga (Blood transfusion = Trasfusione del sangue, 2014)
RH molecular analysis has enabled the documentation of numerous variants of RHD and RHCE alleles, especially in individuals of African origin. The aim of the present study was to determine the type and frequency of D and/or RhCE variants among blood donors of African origin in France, by performing a systematic RH molecular analysis, in order to evaluate the implications for blood transfusion of patients of African origin. Samples from 316 African blood donors, whose origin was established by their Fy(a-b-) phenotype, were first analysed using the RHD and RHCE BeadChips Kit (BioArray Solutions, Immucor, Warren, NJ, USA). Sequencing was performed when necessary. RHD molecular analysis showed that 26.2% of donors had a variant RHD allele. It allowed the prediction of a partial D in 11% of cases. RHCE molecular analysis showed that 14.2% of donors had a variant RHCE allele or RH [RN or (C)ces] haplotype. A rare Rh phenotype associated with the loss of a high-prevalence antigen or partial RhCE antigens were predicted from RHCE molecular analysis in 1 (0.3%) and 17 (5%) cases, respectively. Systematic RHD and RHCE molecular analysis performed in blood donors of African origin provides transfusion-relevant information for individuals of African origin because of the frequency of variant RH alleles. RH molecular analysis may improve transfusion therapy of patients by allowing better donor and recipient matching, based not only on phenotypically matched red blood cell units, but also on units that are genetically matched with regards to RhCE variants.